Radiopacity and flow of different endodontic sealers - Tanomaru-Filho, Mario; Bosso, Roberta; Viapiana, Raqueli; Guerreiro-Tanomaru, Juliane M. (My University, 2013)
The present study evaluated the radiopacity and flow of different endodontic sealers: AH Plus, Endo CPM, MTA Fillapex, Sealapex, Epiphany, and Epiphany SE. For the radiopacity test, six specimens measuring 10 mm in diameter and 1 mm in thickness were fabricated from each material. They were radiographed on an occlusal film alongside an aluminum step wedge. Radiographs were digitized to determine the radiopacity equivalence in millimeters of aluminum. To evaluate the flow, a 120 g load was placed on top of a glass slab containing 0.05 +/- 0.005 mll of sealer. The diameters of each material were measured (mm) with a caliper and samples were photographed. Digitized images were analyzed using the UTHSCSA Image Tool for Windows software, to determine the sealer area (mm2). Data were submitted to ANOVA and Tukey's test at 5% significance. AH Plus and Epiphany SE presented the greatest radiopacity (12.5 mm Al and 12.0 mm Al, respectively) (p > 0.05), followed by Epiphany (9.6 mm Al) and Fillapex (8.9 mm Al). Endo CPM (5.46 mm Al) and Sealapex (5.51 mm Al) presented lower radiopacity. MTA Fillapex presented significantly higher values of flow than other sealers (33.11 mm and 844.9 mm2). AH Plus, Epiphany, and Epiphany SE had similar values. Endo CPM (21.05 mm and 342.8 mm2) and Sealapex (19.98 mm and 352.5 mm2) presented the lowest flow values (p > 0.05). All sealers presented radiopacity and flow values according to ISO and ANSI/ADA recommendations.